Src Tyrosine Kinase Inhibitors: New Perspectives on Their Immune, Antiviral, and Senotherapeutic Potential - Rivera-Torres, José; San José, Esther (Frontiers in Pharmacology, 2019)
Src is the prototypical member of a large family of non-receptor protein-tyrosine kinases. Aberrant and altered expression of these tyrosine kinases has been extensively reviewed in the literature and shown to be involved in a plethora of key cellular processes leading to tumor development and progression. Therefore, Src tyrosine kinases have been considered an essential target for drug development to fight tumor malignancies. Since the approval, by FDA in 2001, of the first Src tyrosine kinase inhibitor (STKI) Imatinib for the treatment of chronic myeloid leukemia (CML), the number of these inhibitors has increased notably, Dasatinib being the most widely studied. STKIs generally act by reducing or stopping the aberrant activity of several tyrosine-kinase family members in tumor cells. A decade ago, scientific evidence pointed to the existence of alternative mechanisms involving key immune cells of the tumor microenvironment (cytotoxic T lymphocytes and NK). Paradoxically, in addition to a well-known immunosuppressive effect preventing T lymphocyte activation, the reported increase in monoclonal and oligoclonal large granular lymphocytosis in a group of Dasatinib-treated patients reduced susceptibility to opportunistic infections and improved the prognosis of CML patients receiving the drug. Herein we review the recent findings on the immunomodulatory properties of STKIs, including the promising role of γδ T-lymphocytes, and their plausible interest in the clinic. Moreover, we will briefly summarize potential benefits, adverse effects and safety concerns regarding viral infections, as well as the ability of STKIs to alleviate age-associated physical dysfunction and their impact.